Chemistry, asked by shivammathur646, 1 year ago

Which of the following statement is correct about heavy water.
(a) Its molar mass is 20 g mol-1.
(b) It is obtained by repeated electrolysis of water. (c) Its density is maximum at 40 C.
(d) Its density is maximum at 11.4 0C.

Answers

Answered by aquakiller013
0

Answer:

Simplifying

(5x + -7)(3x + -4) = 0

Reorder the terms:

(-7 + 5x)(3x + -4) = 0

Reorder the terms:

(-7 + 5x)(-4 + 3x) = 0

Multiply (-7 + 5x) * (-4 + 3x)

(-7(-4 + 3x) + 5x * (-4 + 3x)) = 0

((-4 * -7 + 3x * -7) + 5x * (-4 + 3x)) = 0

((28 + -21x) + 5x * (-4 + 3x)) = 0

(28 + -21x + (-4 * 5x + 3x * 5x)) = 0

(28 + -21x + (-20x + 15x2)) = 0

Combine like terms: -21x + -20x = -41x

(28 + -41x + 15x2) = 0

Solving

28 + -41x + 15x2 = 0

Solving for variable 'x'.

Factor a trinomial.

(4 + -3x)(7 + -5x) = 0

Subproblem 1

Set the factor '(4 + -3x)' equal to zero and attempt to solve:

Simplifying

4 + -3x = 0

Solving

4 + -3x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.

4 + -4 + -3x = 0 + -4

Combine like terms: 4 + -4 = 0

0 + -3x = 0 + -4

-3x = 0 + -4

Combine like terms: 0 + -4 = -4

-3x = -4

Divide each side by '-3'.

x = 1.333333333

Simplifying

x = 1.333333333

Explanation:

Answered by Rndy2004
0

Answer:Simplifying

(5x + -7)(3x + -4) = 0

Reorder the terms:

(-7 + 5x)(3x + -4) = 0

Reorder the terms:

(-7 + 5x)(-4 + 3x) = 0

Multiply (-7 + 5x) * (-4 + 3x)

(-7(-4 + 3x) + 5x * (-4 + 3x)) = 0

((-4 * -7 + 3x * -7) + 5x * (-4 + 3x)) = 0

((28 + -21x) + 5x * (-4 + 3x)) = 0

(28 + -21x + (-4 * 5x + 3x * 5x)) = 0

(28 + -21x + (-20x + 15x2)) = 0

Combine like terms: -21x + -20x = -41x

(28 + -41x + 15x2) = 0

Solving

28 + -41x + 15x2 = 0

Solving for variable 'x'.

Factor a trinomial.

(4 + -3x)(7 + -5x) = 0

Subproblem 1

Set the factor '(4 + -3x)' equal to zero and attempt to solve:

Simplifying

4 + -3x = 0

Solving

4 + -3x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.

4 + -4 + -3x = 0 + -4

Combine like terms: 4 + -4 = 0

0 + -3x = 0 + -4

-3x = 0 + -4

Combine like terms: 0 + -4 = -4

-3x = -4

Divide each side by '-3'.

x = 1.333333333

Simplifying

x = 1.333333333

Read more on Brainly.in - https://brainly.in/question/16835945#readmore

Explanation:

Similar questions